Tropic of chaos climate change and the new geography of violence - Parenti, Christian (Nation Books, 2011)
Journalist Christian Parenti examines the influence of extreme weather which is caused by global warming on unrest and violence in countries located along mid-latitudes and examines how sustainable living among the world's population could solve the problems.